DAQ for commissioning and calibration of a multichannel analyzer of scintillation counters. Issue 9 (1st September 2016) - Tortorici, F.; Jones, M.; Bellini, V.; Sutera, C.; Wojtsekhowski, B.; Mammoliti, F.
ABSTRACT: We report the status of the Data Acquisition (DAQ) system for the Coordinate Detector (CDET) module of the Super Bigbite Spectrometer facility at Hall A of Thomas Jefferson Accelerator Facility. Presently, the DAQ is fully assembled and tested with one CDET module. The commissioning of CDET module, that is the goal of the tests presented here, consists essentially in the measures of the amplitude and time-over-threshold of signals from cosmic rays. Hardware checks, the developing of DAQ control and off-line analysis software are ongoing; the module currently seems to work roughly accordingly to expectations. Data presented in this note are still preliminary.